The Relationship between Technical Skills of Madrasah Heads and Non-Financial Compensation with the Performance of Private Islamic Elementary School Teachers - Lutfiatul Iltiqoiyah; Chanda Chansa Thelma (Journal of Social Studies and Education, 2025)
This study explores the combined influence of the technical skills of madrasah heads and non-financial compensation on the performance of teachers in private Madrasah Ibtidaiyah (MI) schools in Probolinggo Regency, Indonesia. While previous research has examined these factors independently, little attention has been given to their simultaneous impact in the context of Islamic primary education. This research aims to fill that gap by investigating how leadership skills, including educational management abilities, and non-financial incentives, such as career development and recognition, contribute to teacher performance. A quantitative research design with descriptive correlational analysis was used, collecting data from 363 teachers through structured questionnaires. Statistical methods, including Spearman Rank Correlation, revealed strong positive correlations between both technical skills and non-financial compensation with teacher performance. Furthermore, the combined effect of these two factors was found to have a nearly perfect influence on teacher performance. The findings underscore the importance of integrating effective leadership with non-financial incentives to enhance teacher outcomes. This study provides valuable insights for educational leaders and policymakers aiming to improve teacher motivation and performance in Islamic primary schools. The results also suggest directions for future research, including exploring the long-term effects of leadership development and non-financial rewards on teaching quality.